New adverse coronary events in valve-in-valve TAVR and native TAVR—A 2-year matched cohort - Koren, Ofir; Patel, Vivek; Naami, Robert; Naami, Edmund; Nagasaka, Takashi; Shechter, Alon; Natanzon, Sharon Shalom; Kohan, Siamak; Allison, Zev; Lerner, Addee; Cheng, Daniel Eugene; Chakravarty, Tarun; et al. (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE: To assess the incidence of new adverse coronary events (NACE) following transcatheter aortic valve replacement (TAVR) and valve-in-valve TAVR. BACKGROUND: ViV-TAVR is an accepted treatment for degenerative prostheses. TAVR studies have suggested an increased risk of coronary artery (CA) obstruction and flow stasis influencing thrombus formations. Whether contemporary ViV-TAVR is associated with higher NACE than TAVR is unknown. METHODS: We used data from 1224 TAVR patients between 2016 and 2021. We propensity-matched patients following VIV-TAVR and TAVR by significant predictors to overcome confounders in patients’ baseline characteristics and procedural factors. RESULTS: The matched population included 129 patients in each group. In line with prior reports, there was a higher in-hospital CA obstruction trend with VIV-TAVR (3.1 vs. 1.6%; P=0.23). Despite this, two-year cumulative NACE was similar between groups (4.7% vs. 6.2% respectively, p=0.79), with no difference between its components: myocardial infarction (MI) (P=.210), unplanned coronary catheterization (P=.477), or CA bypass graft (CABG)(P=.998). Moreover, hypoattenuated leaflets thickening (HALT) at 30-day CT was observed in nearly a quarter of the patients with no difference between groups (23.9 vs. 23.1%, HR 1.02, 95% CI 0.50-1.28, p=.872). The progression rate of the CA calcium score (CACS), assessed in a third of patients, was no difference between groups (Plog-rank=0.468, 95% CI 0.12-1.24). Low CA height was an unfavorable predictor for in-hospital coronary obstruction and 2-year NACE (HR 1.20 and HR 1.25, P=.001 and P<.0001, respectively). CONCLUSION: At a 2-year follow-up, ViV-TAVR was not associated with a higher rate of MI, unplanned catheterization, CABG, or HALT.